Character Building Strategy In Early Children - setyowati, rina insani; Hayeemaming, Marwan; Shofwan, Arif Muzayin (Journal of Childhood Education, Development and Parenting, 2023)
Character building in early childhood requires a strategy. Without the right strategy, character building will be difficult to realize. This descriptive qualitative research with literature study examines the strategy of character building in early childhood. The data analysis technique uses analysis content by sorting out data according to the objectives and research problems. This paper produces the following things. First, the character development strategy in early childhood can be done in two ways, namely: (1) integration in daily activities, can be done by example, spontaneous activities, reprimand, environmental conditioning, and routine activities; (2) integration in programmed activities, which is carried out after the teacher first makes a plan for the values ​​that will be integrated in certain activities. Second, other strategies to develop character education include: applying learning methods that involve the active participation of students; create a conducive learning environment; provide explicit, systematic, and continuous character education; using teaching methods that take into account the uniqueness of each child; build supportive and caring relationships in the classroom and throughout the school; build positive behavior models; create opportunities for students to be active and meaningful, including in classroom and school life; and others